2014
DOI: 10.4103/0253-7613.129334
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis following intravenous ranitidine: A rare adverse reaction of a common drug

Abstract: Ranitidine hydrochloride is a widely used drug that is generally well-tolerated. Anaphylaxis is rarely observed with ranitidine. We report a case who developed severe anaphylaxis following single dose of intravenous ranitidine. The article highlights the importance of recognition of this serious adverse event and re-emphasizes the need for cautious use of drugs, especially in those with known history of allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This is the first case of anaphylaxis to ranitidine in pediatric age; anyway, both treatment and timing of presentation are the same as those reported in the literature [1]. …”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This is the first case of anaphylaxis to ranitidine in pediatric age; anyway, both treatment and timing of presentation are the same as those reported in the literature [1]. …”
Section: Discussionmentioning
confidence: 77%
“…Recently, a review collecting all reported cases of anaphylaxis to ranitidine has been published [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Hypersensitivity reactions are unusual, most of them are immediate type reactions, usually expressed as mild manifestations such as pruritus or acute maculopapular eruptions without other systemic symptoms [17,18]. Nonetheless, severe reactions such anaphylaxis or angioedema [15][16][17] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported ranitidine-induced anaphylaxis. [ 4 ] Antonicelli et al . in 2012 and Sripriya et al .…”
Section: Discussionmentioning
confidence: 99%